Small Antennas for Wireless Micro-Systems - Rainer Wansch (Active and Passive Electronic Components)
This paper will describe the topology of wireless micro-systems networks and some of their key components. In particular we will deal with the antennas: loops, helices, F-antennas, patches and dielectrically loaded antennas.